(untitled) (Journal of Libya for geographical studies, 2023)
This research is about misleading the light on the trend of growth in population growth and the average in revealing the suffering resulting from the need in the areas that increase as the planning increases, and in many residential areas they turn into their homes, the giving house, the historical approaches, and the analytical approaches during the period 2004 -2005. 2006 and projections until the year 2030 AD. Several results and recommendations were reached, the most important of which are: This means that in the study area in 2006 there were about 10,153 housing units, with 11,957 Libyan families corresponding to them, meaning that 1,804 families are without housing (they live inside other housing), and this means that 15 % of the total population of the region has no housing, and that the average population growth rate will be 1.73%,%, thus the population in 2030 will be about 97,660 people, and the houses that will be in good condition do not exceed 2,843 houses, and the need of the residents of the region for housing units will reach 14,813 housing units, meaning the region needs to build 2,116 housing units annually until 2030 AD, and the suffering will not remain for many families Without housing, therefore, it is recommended to move towards vertical construction at an estimated rate of 50%, and to use prefabricated buildings due to their low economic costs during the first implementation stages.